Definition of an EU-DEMO design point robust to epistemic plasma physics uncertainties - M. Coleman; H. Zohm; C. Bourdelle; F. Maviglia; A.J. Pearce; M. Siccinio; A. Spagnuolo; S. Wiesen (Nuclear Fusion)
A novel approach for explicitly and robustly accounting for epistemic uncertainties in plasma confinement in the 0D design of tokamaks is presented, in which the plasma safety factor at the 95th percentile flux surface, q _95 , is used to apply a design margin on confinement in terms of the H-factor, H . The PROCESS code is used to explore the EU-DEMO design space in terms of aspect ratio, major radius, q _95 , and net electric power, $P_{el,net}$ using the above approach. A comprehensive account of the input assumptions and underlying models used is given. We formulate a proposal for a new EU-DEMO design point which addresses some key shortcomings of the previous design point (EU-DEMO 2017 (Wenninger and Kembleton 2017 Technical Report EFDA_D_2NDSKT (EUROfusion); Siccinio et al 2022 Fusion Eng. Des. 176 113047)), in particular by the inclusion of an explicit and quantified design margin for epistemic confinement uncertainties, and a considerable reduction in divertor heat loads during re-attachment. We find that self-consistently including a size-able margin on confinement using our approach considerably reduces the potential $P_{el,net}$ of a reactor, compared with no margin. However, we argue that by doing so, the engineering design of future tokamak fusion power plants can effectively be insulated from epistemic confinement uncertainties insofar as possible, facilitating the design process.